Child and adolescent obesity in Ireland: A longitudinal perspective - David Madden (University College Dublin, UCD School of Economics, 2016)
This paper examines developments in childhood and adolescent obesity in Ireland using two waves of the Growing Up in Ireland survey. Obesity appears to level off between the two waves though there is tentative evidence that the socioeconomic gradient, measured with respect to maternal education and family income, becomes steeper. Exploiting the longitudinal nature of the data, transitions into and out of obesity are examined, with higher rates of transition into obesity observed for those whose mothers have the lowest level of education. Decomposition of the concentration index with respect to income reveals a greater role for income related obesity mobility rather than obesity related income mobility.
Keywords: I12; I14; 330; Obesity; socioeconomic gradient; longitudinal